2017
DOI: 10.1007/s11356-017-9323-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of heat-inactivated marine Aspergillus flavus as a novel biosorbent for removal of Cd(II), Hg(II), and Pb(II) from water

Abstract: A novel marine fungus was isolated and classified as Aspergillus flavus strain EGY11. The heat-inactivated form of isolated Aspergillus flavus was investigated and evaluated as a new eco-friendly and highly efficient biosorbent for removal of toxic heavy metals such as Cd(II), Hg(II), and Pb(II) from aqueous solutions. The SEM morphological studies of biosorbent-loaded metal ions confirmed their direct binding on the surface of heat-inactivated Aspergillus flavus. The metal biosorption capacity values were det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…For example, when the dosage changed from 0.05 g·L −1 to 0.4 g·L −1 , the removal efficiencies of acenaphthene (ACE), PHEN, and fluoranthene (FLUOR) escalated from 14.4% to 41.3%, 27.3% to 72.6%, and 54.6% to 85.8%, respectively. Similar trends have been reported for metal ions and dyes on several biosorbents [37,38]. …”
Section: Effects Of Dosagesupporting
confidence: 86%
See 1 more Smart Citation
“…For example, when the dosage changed from 0.05 g·L −1 to 0.4 g·L −1 , the removal efficiencies of acenaphthene (ACE), PHEN, and fluoranthene (FLUOR) escalated from 14.4% to 41.3%, 27.3% to 72.6%, and 54.6% to 85.8%, respectively. Similar trends have been reported for metal ions and dyes on several biosorbents [37,38]. …”
Section: Effects Of Dosagesupporting
confidence: 86%
“…The peak near 1650 cm −1 denotes the aromatic C=C and C=O asymmetric stretching vibrations [7,35]. A characteristic peak at 1730 cm −1 was formed due to the vibration of C=O at the -COOH stretching frequency [37]. The result confirmed that the bacterial surface was abundant in carboxyl, amino groups, saturated and unsaturated aliphatic carbons, and aromatic structures.…”
Section: Methodsmentioning
confidence: 67%
“…59, No.1 (2019) MaNal Tawfeek el-Sayed measured. Adsorptive removal of heavy metals from water samples was performed by passing 1L solution through a microcolumn with length, 10cm, and internal diameter, 0.5cm packed with 1g of dried Y. lipolytica biomass according to Mahmoud et al (2017).…”
Section: Application Of Dried Y Lipolytica Aumc 9256 Biosorbent To Ementioning
confidence: 99%
“…24 Similar trends had been observed for the biosorption of metals, dyes, uranium and organic compounds onto several biosorbents. 17,21,38 In addition, the biosorption processes of phenanthrene and iodine were found to reach their optimum conditions at the dosage of 0.75 g L À1 (Fig. 2a), where the biosorption capacities caught 900 and 11 600 mg kg À1 , respectively.…”
Section: Biosorption Of Phenanthrene and Iodine By Sibb In Single Andmentioning
confidence: 93%
“…The use of natural biomaterials (served as adsorbents) is considered promising and the most attractive alternative due to their easy handling, versatility, costeffectiveness, efficiency, low-selectivity and relative abundance compared with conventional techniques. [13][14][15] Studies have reported that dead or metabolically inactive biomass materials were used as successful biosorbents for the treating or removal of dyes, [16][17][18][19] heavy metals, [20][21][22][23] HOCs [24][25][26] and radioactive elements such as uranium 27,28 from aqueous solutions. Several mechanisms were also proposed and summarized as follows: 29 (1) electrostatic binding for some cationic metals, dyes and radioactive elements due to negative groups in biosorbents; 16,27,30 (2) hydrophobic interactions and partitioning for hydrophobic organic compounds; 26,31 (3) specic molecular-level interactions such as cation-p interactions; 32 and (4) deposition on the cell surface or within the cell wall structures.…”
Section: Introductionmentioning
confidence: 99%